Developing Basic Accounting E-Module Based on Scientific Approach in Vocational High Schools - Fahrurrozi, Muh; Mohzana, Mohzana; Mispandi, Mispandi; Murcahyanto, Hary (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to produce a basic accounting economics e-module based on a scientific approach to increase learning motivation and understanding for students of Vocational High Schools. In addition, this study aims to analyze the feasibility and effectiveness of basic accounting e-modules based on a scientific approach developed based on the results of expert design, material, and student responses. This research applied the Thiagarajan 4-D model through the following steps: Define, Design, Develop, and Disseminate. Two model instruments were implemented upon expert judgements; assessment form of content (material) expert and assessment from media expert. To display, all data collected was processed qualitatively and quantitatively. It involved student responses and numerical data (via questionnaires and validation forms) from both experts. The results showed that (1) the development of the Basic Accounting E-Module Based on the Scientific Approach in vocational high school grade X implements the 4D model up to the development stage, (2) the assessment from media design experts obtained is 91%, which means '"very feasible" and the material expert assessment obtained is 92% which means '"very feasible," (3) The results of the responses of class X students of vocational high school in limited trials obtained an average score of 84% with the category "Very Feasible" and in the field, tests obtained an average overall score of 94% with the category "Very feasible." The module can widely impact better content of teaching basic accounting as a measurable guide for prospective school teachers.